Protecting privacy in China a research on China's privacy standards and the possibility of establishing the right to privacy and the information privacy protection legislation in modern China - Wang, Hao (Springer, 2011)
Today, privacy is one of the most hotly debated topics worldwide. The book aims to balance the development of personal rights in a country that has historically valued collective rights over those of the individual. The protection of privacy is not an issue that has been emphasised during the rapid development of economic laws in China. However, the accompanying development of greater government-based regulation of these laws? implementation has led to greater invasions of personal privacy. This study attempts to provide a way forward for China to address the ever-increasing concerns about the protection of privacy and puts forward a legislative model for protection. This is achieved after - a thorough analysis of the threats to privacy protection in China, - a critical evaluation of the level of current privacy protection in China, and - an analysis of the privacy laws in a series of developed nations based on common law and civil law.